Recrudescence of Scarlet Fever and Its Implications for Dental Professionals - Victor Haruo Matsubara; Janina Christoforou; Lakshman Samaranayake (Elsevier, 2023)
A significant increase in the incidence of scarlet fever, mainly in Europe, has been noted during the COVID-19 postpandemic period. Scarlet fever is caused by a pyrogenic exotoxin-producing streptococcus-Streptococcus pyogenes-responsible for more than 500,000 deaths annually worldwide. Superantigens (SAgs) secreted by this Group A streptococcus (GAS) usually overstimulate the human immune system, causing an amplified hypersensitivity reaction leading to initial symptoms such as sore throat, high fever, and a sandpaper-like skin rash. There could be concurrent oral manifestations known as "strawberry tongue" or "raspberry tongue," which may be first noted by oral health professionals. The early diagnosis and treatment of this disease is critical to obviate the development of local and systemic sequelae such as acute rheumatic fever, endocarditis, and glomerulonephritis. Antibiotics should be prescribed early to mitigate its duration, sequelae, and community spread. Dental practitioners should be aware of the early symptoms of scarlet fever for infection detection, emergency patient management, and appropriate referral. This concise review outlines the prevalence, pathogenicity, oral and systemic manifestations, as well as the dental implications of scarlet fever.